"Spiraling up": Using ripple effect mapping to evaluate how an extension volunteer program increases community development capacity. Issue 1 (1st January 2021) - Bloom, J. Dara
ABSTRACT: Evaluation metrics that assess the impacts of Cooperative Extensionprogramming focus on quantifiable indicators that may overlookbroader community-level changes. This study addresses this by usingthe "spiraling up" theory of change and Ripple Effect Mapping to assesshow volunteers build Cooperative Extension's communitydevelopment capacity. Focusing on Family and Consumer Scienceagents and volunteers in the North Carolina Extension Master FoodVolunteer program, analysis focused on whether volunteers increasedExtension's bonding and bridging social capital to create a process ofexpanded community engagement. Findings indicate that volunteershelped Extension agents reach new areas, organizations, andpopulations, expanding impacts and increasing community access toresources, as suggested by the "spiraling up" theory of change. Thecommunity relationships fostered by volunteers are a key first step toincreasing Extension's capacity to affect institutional and communitylevelchanges, which provides lessons for organizations that use healthand wellness programs to promote community development.